Immunomodulatory Effects of Multistrain Probiotics (Protexin™) on Broiler Chicken Vaccinated Against Avian Influenza Virus (H9) - Ghafoor, Aamir; Naseem, Shamoon; Younus, M.; Nazir, Jawad (International Journal of Poultry Science, 2005)
This study was undertaken to evaluate the effects of probiotics (Protexin) on the immune response of broiler chicks. The parameters of investigation were hemagglutination inhibition HI titer of antibodies against avian influenza virus and post field AIV challenge. The findings were compared with the cyclophosphamide treated AIV-vaccinated; untreated and AIV-vaccinated and unvaccinated and control birds this investigation revealed that protexin treated chicks have higher AIV-HI antibody and no AIV post challenge mortality compared to the cyclophosphamide treated and untreated chicks the overall finding of this study clearly demonstrate that the use of this multistrain probiotics has good effect on immune response of broiler chicks.